Impact of ozonation on the formation of particulate nitrosodi-methylamine (NDMA) in atmosphere - Choi, Na Rae; Kim, Yong Pyo; Lee, Ji Yi; Kim, Eunhye; Kim, Soontae; Shin, Hye Jung (Chemosphere, 2024)
The contribution of ozonation to the formation of particulate nitrosodi-methylamine (NDMA) in the aqueous aerosol phase was investigated using measurement data from 2018 in Seoul, Republic of Korea and a box model. The correlation between the NDMA concentration and aerosol liquid water content and box model results showed that aqueous aerosol phase reactions, including nitrosation and ozonation, might contribute to the formation of NDMA. The concentration of NDMA and the ratio of O3/dimethylamine exhibited a negative correlation, suggesting that the contribution of ozonation to NDMA formation may not be significant. Furthermore, when the daily concentration of NDMA exceeded 10 ng/m3, the pH was 3.96 ± 0.48, indicating that the impact of ozonation on NDMA concentration might not be significant. To quantitatively investigate the contribution of ozonation, the ozonation mechanism that forms NDMA was included in the box model developed in our previous study. The model results showed that the ozonation contributed to the ambient concentration of NDMA (7.9 ± 3.8% (winter); 1.9 ± 3.0% (spring); 10.0 ± 0.77% (summer); 3.6 ± 7.3% (autumn)). It is estimated that the relatively higher O3/NOx ratio in summer (1.63 ± 0.69; 0.64 ± 0.52 (winter); 1.14 ± 0.92 (spring); 0.52 ± 0.54 (autumn)) could enhance ozonation and that relatively lower pH in summer (2.2 ± 0.4; 5.3 ± 1.2 (winter); 3.9 ± 1.2 (spring); 3.9 ± 0.7 (autumn)) could hinder nitrosation compared to that in other seasons.
Keywords: Aerosol phase; Aqueous aerosols; Box models; Liquid water content; Measurement data; Modeling results; Nitrosation; Nitrosodi-methylamine; Particulates; Seoul; Aerosols; Atmosphere; Dimethylnitrosamine; Hydrogen-Ion Concentration; Methylamines; Ozone; Water; Water Pollutants, Chemical; Water Purification; Liquid water content; Nitrosamine; Nitrosation; Nitrosodi-methylamine (NDMA); Ozonation; Seoul